The dynamics of Communal conflicts and criminality in Nigeria (2015)
Communal conflicts have arisen out of the context of mutual fear and suspicion over unequal distribution of socio-political and economic goods and lack of cordiality. Since most of the perpetrators and mercenaries who execute the conflicts are usually in possession of arms and ammunitions, it becomes very easy for them to perpetuate various criminal acts. This paper therefore examined the dynamics of communal conflicts and criminality in Nigeria. This paper demonstrated that communal conflicts engendered criminality in Nigeria,' however, little or nothing is known about the criminality angle/dimension of the incessant communal conflicts in Nigeria. The paper therefore recommended among others that, there is urgent needs for structural reforms to address the issues of poverty, social inequality, injustice and oppress ion so as to avoid situations that create communal conflicts. Governments should endeavour at all levels to work with the various communities to promote harmonious relationship among the various ethnic affiliations through the building of inter-ethnic civil networks at the community level which can be targeted for skills and capacity building/development programmes as a strategy for conflict management.